If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5a + 3 = 4 + a Reorder the terms: 3 + 5a = 4 + a Solving 3 + 5a = 4 + a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1a' to each side of the equation. 3 + 5a + -1a = 4 + a + -1a Combine like terms: 5a + -1a = 4a 3 + 4a = 4 + a + -1a Combine like terms: a + -1a = 0 3 + 4a = 4 + 0 3 + 4a = 4 Add '-3' to each side of the equation. 3 + -3 + 4a = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 4a = 4 + -3 4a = 4 + -3 Combine like terms: 4 + -3 = 1 4a = 1 Divide each side by '4'. a = 0.25 Simplifying a = 0.25
| 4(36)+9y=36 | | 6x^2-3x-2=0 | | 2(2x-5)=3(x-2) | | 7y^3-28y=0 | | 2/3a-11=4+a | | 5M-1=-70-151 | | (9x-2)(7x+3)= | | 8n-3=13 | | (10q-3)(q+11)=0 | | 4x+9(36)=36 | | 4=39-9y | | 12=6+2n | | 3(2x-1)+(x-3)=0 | | x(x-9)=15 | | 8=2x-5 | | 6x-75x=100 | | (3q-2)(q-7)=0 | | 3/7x=21 | | 4x^2-44x+112= | | (3p-2)(q-7)=0 | | 1/7/8/9 | | 3x+35x=76 | | 12x=2x | | -2+1=3x-5 | | 2/5h-7=12/5h-2h | | w+1/5=7/8 | | (9p-4)(p+9)=0 | | 8=4m-4 | | 4+(-3/5)x=16 | | n/0.6=662/3 | | 2p^3+30p^2-68p= | | 86-2x=60 |